Некоторые особенности строения пищеварительной и выделительной систем клеща Phytoseiulus persimilis Athias-Henriot (Parasitiformes, Phytoseiidae) - Старовир, И.С. (Вестник зоологии, 1973)
The structure of the digestive and- excretory systems in Phytoseiulus persimilis is described. It is established that the digestive system in Ph. persimilis is similar on the whole to the digestive system of other gamasid mites, though there are also some morphofunctional differences (no folding in the intestine and diverticula, etc.). Three types of digestive cells secretory, digestive and undifferentiated ones are characterized. The study of the digestive system morphology resulted in detecting some functional singularities of the Phytoseiulus persimilis nutrition.